PENETAPAN ANGKA PEROKSIDA MINYAK GORENG CURAH SAWIT PADA PENGGORENGAN BERULANG IKAN LELE - Amelia handayani burhan (JURNAL PENDIDIKAN SAINS UNIVERSITAS MUHAMMADIYAH SEMARANG, 2018)
Culinary pecel catfish or fried catfish are in great demand in Yogyakarta. The habit of using palm oil for cooking repeatedly has an economic value for the seller, but has a bad potential for the health of consumers. One of the causes is the increase of the oil peroxide number due to heating process. Peroxide in the long term in the body can cause destruction of vitamin E which is useful to ward off free radicals. This study aims to determine the maximum repetition of palm oil used in the process of frying catfish. A number of bulk oils are used to fry fifteen catfish with frying repetitions five times in constant fire. Oil taken on each fryer is inserted in a bottle in a cold state. The peroxide number on each oil sample was determined by iodometric method using 0.01 Nodium Thiosulfate solution and starch indicator. The results show that the peroxide number of oil palm before and after oil was used to fry the catfish on the fryer to 1, 2, 3, 4 and 5 respectively: 0.3198; 2.2707; 3,1022; 3,7738; 4,6063 and 11,0341 mekO2 / kg, wherein the 5th frying peroxide number has exceeded the SNI limit.